2020
DOI: 10.3390/sym12020229
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Particle Swarm Optimization into Improved Bacterial Foraging Optimization Algorithm Applied to Classify Imbalanced Data

Abstract: In this paper, particle swarm optimization is incorporated into an improved bacterial foraging optimization algorithm, which is applied to classifying imbalanced data to solve the problem of how original bacterial foraging optimization easily falls into local optimization. In this study, the borderline synthetic minority oversampling technique (Borderline-SMOTE) and Tomek link are used to pre-process imbalanced data. Then, the proposed algorithm is used to classify the imbalanced data. In the proposed algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Ye et al reported "Incorporating Particle Swarm Optimization into Improved Bacterial Foraging Optimization Algorithm Applied to Classify Imbalanced Data" [7]. In this paper, particle swarm optimization is incorporated into an improved bacterial foraging optimization algorithm, which is applied to classify imbalanced data to solve the problem of how original bacterial foraging optimization easily falls into local optimization.…”
Section: Lan Et Al Reported "Symmetric Modeling Of Communication Effectiveness and Satisfactionmentioning
confidence: 99%
“…Ye et al reported "Incorporating Particle Swarm Optimization into Improved Bacterial Foraging Optimization Algorithm Applied to Classify Imbalanced Data" [7]. In this paper, particle swarm optimization is incorporated into an improved bacterial foraging optimization algorithm, which is applied to classify imbalanced data to solve the problem of how original bacterial foraging optimization easily falls into local optimization.…”
Section: Lan Et Al Reported "Symmetric Modeling Of Communication Effectiveness and Satisfactionmentioning
confidence: 99%
“…Ye et al 24 have integrated PSO in improved bacterial foraging optimization algorithm for classifying imbalanced data. Borderline‐SMOTE and Tomek link are first used to preprocess the dataset.…”
Section: Introductionmentioning
confidence: 99%
“…The Bacterial Foraging Optimization (BFO) algorithm is a new swarm intelligence optimization technique that possesses a series of advantages including insensitivity to initial values and parameter selection, strong robustness, simplicity, ease of implementation, parallel processing and global search [31]. BFO has been applied in a wide range of optimization problems such as the energy forecasting [32], expert energy management considering the uncertainty [33], the imbalanced data classification [34], and robotic cell scheduling [35]. The advantages of BFO against conventional swarm intelligence approaches greatly encourages us to solve the problems in enhancing the train driving control profiles and evaluate the energy saving space of the train scheduling schemes.…”
Section: Introductionmentioning
confidence: 99%